2021
DOI: 10.21608/jhiph.2021.163875
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and Survival of Childhood Malignancies: A 10-Year Retrospective Study

Abstract: Background: Hematopoietic neoplasms constitute more than 40% of malignancies in children and represent a wide range of disorders, including acute leukemias and lymphomas. Childhood cancer is curable if diagnosed early, and the survival has improved dramatically over the last 20 years due to aggressive combined modality management. Objective: To estimate the proportion of hematologic malignancies, identify patient characteristics, and calculate the overall and event-free survival of childhood malignancies at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In the current study, the mean age for hematologic malignancies was 7.4±3.0 years and ranged from 2 to 15 years. Similarly, Rodriguez-Abreu et al (12) reported that hematological malignancies could occur at any age and 35% of leukemia cases occurred in an age ranged from 0 to 14 years. Also, Al-Kahiry (8) reported that 33% of hematological malignancies in children occurred from 0 to 14 years with a peak from birth to the age of 2 years and then fall.…”
Section: Discussionmentioning
confidence: 89%
“…In the current study, the mean age for hematologic malignancies was 7.4±3.0 years and ranged from 2 to 15 years. Similarly, Rodriguez-Abreu et al (12) reported that hematological malignancies could occur at any age and 35% of leukemia cases occurred in an age ranged from 0 to 14 years. Also, Al-Kahiry (8) reported that 33% of hematological malignancies in children occurred from 0 to 14 years with a peak from birth to the age of 2 years and then fall.…”
Section: Discussionmentioning
confidence: 89%